Zinc-Containing Metalloenzymes: Inhibition by Metal-Based Anticancer Agents - Ye, Ruirong; Tan, Caiping; Chen, Bichun; Li, Rongtao; Mao, Zongwan (Frontiers in Chemistry, 2020)
DNA has been considered as the target of platinum-based anticancer drugs which are gained great success in clinics, but DNA-targeted anticancer drugs cause serious side-effects and easily acquired drug resistance, which stimulates the search for novel therapeutic targets. In the past few years, substantial research has demonstrated that zinc-containing metalloenzymes play a vital role in the occurrence and development of cancer, and they have been identified as alternative targets for metal-based anticancer agents. Metal complexes themselves also have exhibited a lot of appealing features for enzyme inhibition, such as: (i) the facile construction of 3D structures that can increase the enzyme-binding selectivity and affinity; (ii) the intriguing photophysical and photochemical properties, redox activities of metal complexes can offer the possibility to design enzyme inhibitors with multiple modes of action. In this review, we discuss recent examples of zinc-containing metalloenzyme inhibition by metal-based anticancer agents, especially on three zinc-containing metalloenzymes overexpressed in tumors, including histone deacetylases (HDACs), carbonic anhydrases (CAs) and matrix metalloproteinases (MMPs).